The Relationship between Free Cash Flow and Agency Costs (Survey of Banks in Damascus Securities Exchange) (Journal of Hama University, 2020)
The Objective of this Research is to determine the nature of the relationship between free cash  flow measured by subtracting net cash flows from operational Activities from net cash flows resulting from investment activities and agency costs measured by the utilization of assets representing the ratio of net sales to total assets and the operating expenses representing the ratio of total operational expenses to net sales, in sample of 14 banks included in Damascus Securities Exchange during the period (2013-2017),In order to achieve the objectives of the research, the descriptive approach was used on the basis of the survey strategy and the analysis of the correlation ( the pearson correlation analysis) in the statistical SPSS analysis search hypothesies tested, The Research found that there was correlation relationship no significant moral between free cash flow and utilization of assets, and that there was correlation relationship no significant moral between free cash flow and rate of operational expenses, There is no moral relationship  between free cash flow and cost agency in the banks in Damascus Securities Exchange.